74 Rotashock left main bifurcation primary angioplasty with balloon pump support and intravascular image guidance. (6th June 2022) - Dargan, James; Miles, Chris; Wilson, Simon; Khan, Faisal
Abstract : A 64 year old male was brought to a tertiary cardiac centre following collapse preceded by central chest pain and presyncope. On arrival the patient had ventricular fibrillation with return of spontaneous circulation after one direct current cardioversion with a resulting blood pressure of 50/30 mmHg. Past history is hypertension, hypothyroidism and smoking.Electrocardiogram showed sinus rhythm with widespread ST depression but ST elevation in aVR.The patient was taken directly to the cardiac catheter laboratory and found to have critical distal left main stem (LMS) disease. Ostially occluded left anterior descending (LAD) with heavy calcification. Dominant left circumflex (LCx) with heavy proximal calcification and occlusion. Critical proximal ramus disease. The right coronary was not imaged. An intra-aortic balloon pump (IABP) was placed via the right femoral artery. Heparin and tirofiban were given. A 7F EBU guide engaged via the right radial artery. Wires were advanced down LAD and LCx and semi-compliant balloons were inflated in each limb, and although constrained, successfully restored flow. Intravascular ultrasound (IVUS) showed nodular and concentric LAD ostial and concentric LCx calcification. The LAD wire was exchanged via microcatheter for a rotawire and LCx wire removed. 1.75 mm burr rotablation was performed with multiple runs and different guide angles between 140 and 170 thousand revolutions per minute to LMS-LAD. The ramus was wired, pre-dilated and treated with a drug coated balloon. Shockwave intra-vascular lithotripsy to LAD and LCx. Following pre-dilatation with non-compliant balloons the patient received LMS-LAD-LCx culotte bifurcation PCI with Megatron drug eluting stents (DES) using 6 mm balloon for LMS optimisation. Following sequential then kissing balloon inflations, IVUS showed under-expansion of the LCx stent and distal stent edge plaque. A synergy DES was placed to cover the distal stent edge. Further post dilatation and final kissing inflation was undertaken. Final minimum stent area; LMS 18 mm2, LAD 12 mm2 and LCx 9 mm2 with TIMI 3 flow. Minor nipping of ramus ostium was accepted. The patient had a period of recovery on the coronary care unit with dobutamine and IABP support. This was weaned over 36 hours and he went on to make a full clinical recovery.Rotational atherectomy is typically avoided in STEMI due to risk of no-reflow. Given the acuity of the clinical scenario and the challenging bulk of calcium seen it was felt the benefits of this technique outweighed the risks. Rotational atherectomy provides treatment to superficial calcium and shockwave therapy added further, deeper, calcium modification. This case demonstrates the role of RotaShock in primary percutaneous coronary intervention. In this case we were able to perform complex calcium modification techniques in a patient in extremis requiring mechanical circulatory support with excellent radiological and ultimately clinical result. Conflict of Interest: No conflicts to declare.